Shelf-Life of Chlorine Solutions Recommended in Ebola Virus Disease Response - Iqbal, Qais; Lubeck-Schricker, Maya; Wells, Emma; Wolfe, Marlene K.; Lantagne, Daniele (PLOS ONE, 2016)
In Ebola Virus Disease (EVD) outbreaks, it is widely recommended to wash living things (handwashing) with 0.05% (500 mg/L) chlorine solution and non-living things (surfaces, personal protective equipment, dead bodies) with 0.5% (5,000 mg/L) chlorine solution. Chlorine solutions used in EVD response are primarily made from powdered calcium hypochlorite (HTH), granular sodium dichloroisocyanurate (NaDCC), and liquid sodium hypochlorite (NaOCl), and have a pH range of 5–11. Chlorine solutions degrade following a reaction highly dependent on, and unusually sensitive to, pH, temperature, and concentration. We determined the shelf-life of 0.05% and 0.5% chlorine solutions used in EVD response, including HTH, NaDCC, stabilized NaOCl, generated NaOCl, and neutralized NaOCl solutions. Solutions were stored for 30 days at 25, 30, and 35°C, and tested daily for chlorine concentration and pH. Maximum shelf-life was defined as days until initial concentration fell to <90% of initial concentration in ideal laboratory conditions. At 25–35°C, neutralized-NaOCl solutions (pH = 7) had a maximum shelf-life of a few hours, NaDCC solutions (pH = 6) 2 days, generated NaOCl solutions (pH = 9) 6 days, and HTH and stabilized NaOCl solutions (pH 9–11) >30 days. Models were developed for solutions with maximum shelf-lives between 1–30 days. Extrapolating to 40°C, the maximum predicted shelf-life for 0.05% and 0.5% NaDCC solutions were 0.38 and 0.82 hours, respectively; predicted shelf-life for 0.05% and 0.5% generated NaOCl solutions were >30 and 5.4 days, respectively. Each chlorine solution type offers advantages and disadvantages to responders, as: NaDCC is an easy-to-import high-concentration effervescent powder; HTH is similar, but forms a precipitate that may clog pipes; and, NaOCl solutions can be made locally, but are difficult to transport. We recommend responders chose the most appropriate source chlorine compound for their use, and ensure solutions are stored at appropriate temperatures and used or replaced before expiring.